The impact of exchange rate volatility on trade: Evidence for the Czech Republic - Oxana Babecká Kucharčuková (Charles University in Prague, Institute of Economic Studies (IES), 2014)
This paper aims to quantify the impact of nominal exchange rate volatility on nominal trade flows with a particular focus on the Czech Republic. The paper shows that the magnitude of the impact differs when a dynamic model is used instead of static model.
Keywords: F14; F31; F4; 330; Gravity model of trade; Exchange rate volatility; Poisson estimator